ANALISIS FINANSIAL DENGAN PENDEKATAN COST VOLUME PROFIT PADA USAHA KOPI BUBUK BUKIT BARISAN DI KABUPATEN BENGKULU TENGAH - Hervito, Fiqro Ajnus; Kurniati, Novitri; Mutmainnah, Elni (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
The purpose of this study is to estimate the amount of Bukit Barisan Coffee's operating profit that is reflected in the contribution margin, breakeven point, margin of safety (MOS), degree of operating laverage (DOL) and calculate profit target in next period. The research method used is a case study. The analysis used is cost-volume-profit analysis (CVP). The data used are primary and secondary data. Based on the results of the analysis, it was found that the profit was IDR 18,323,806 / month with a production of 896 kg / month, a contribution margin of IDR 21,028,250, a break even point of IDR 6,630,105 and 115 kg of ground coffee, a MOS value of IDR 44,921,895 and a DOL value of IDR 1.15. The planned profit target of IDR 20,156,186 can be achieved if sell 974 kg of coffee or get sales of IDR 55,757,635. To achieve the profit target, an alternative scenario is used to increase sales volume by 10% and a fixed selling price.